Seasonal dynamics of trophic status for zooplankton in the Okhotsk Sea (on the data of testing the stable isotopes of C and N) - Konstantin M. Gorbatenk; Artem E. Lazhentsev; Sergey I. Kiyashko (Известия ТИНРО)
Stable isotopes composition is determined for carbon and nitrogen in tissues of 42 zooplankton species collected in the entire Okhotsk Sea in spring, summer, and autumn. These data allow to define trophic status of the animals and its seasonal variations. By d15N value, the trophic position heightens in the order: omnivorous copepods < euphausiids < hyperiids < jellyfishes < arrowworms, so the filtering copepod Eucalanus bungii has the lowest d15N value (6.9-8.0 ‰) and the arrowworm Sagitta elegans - the highest one (12.0-13.5 ‰). The hierarchy does not change seasonally, but d15N decreases in summer for majority of species that reflects trophic consequences of phytoplankton spring bloom. The dwellers of the shelf have higher d13С values in comparison to the inhabitants of the deep-water sea, and seasonal variation of d13С could be reasoned by seasonal transfers of some zooplankton species between these bathymetric zones.